Construction Financing in Ukraine: Analysis of the Current State, Trends, and Directions for Enhancing Investment Resource Mobilization - Velychko , A. (Ways to Improve Construction Efficiency, 2023)
The article analyzes the current state, key trends and features of construction financing in Ukraine for 2020–2022. A quantitative analysis of the dynamics and structure of capital investments in the construction sector using official statistical data was conducted. The dominance of construction enterprises' own funds and a significant reduction in the share of bank, state and foreign financing were identified. The key factors of the decline in investment activity during this period were identified: the COVID-19 pandemic, macroeconomic instability and full-scale war. The main problems of attracting investment resources to the industry were identified: a shortage of long-term capital, high cost of loans, underdevelopment of the mortgage market, regulatory barriers, corruption risks and low level of investor confidence. To increase the attraction of investment resources in the conditions of prolonged economic instability and full-scale war, it is proposed to implement a comprehensive state policy aimed at diversifying sources of financing and developing alternative instruments: public-private partnership, crowdfunding and specialized investment funds. The need to improve the regulatory framework, strengthen state guarantees, transparency of permitting procedures and intensify cooperation with international financial organizations is substantiated. Special attention is paid to expanding cooperation with the World Bank, the European Bank for Reconstruction and Development, the European Investment Bank and other institutions by attracting loans, grants and insurance of war risks, which will contribute to the return of foreign investors. The expediency of the participation of Ukrainian construction companies in the implementation of international projects for the reconstruction of housing, infrastructure and the social sphere is emphasized. The outlined directions will contribute to the creation of a favorable investment environment, sustainable development and increased competitiveness of construction enterprises in the context of the post-war recovery of the Ukrainian economy.